The Madrid classification of dry eye syndrome-own comments - Świtka-Więcławska, Iwona; Kęcik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The dry eye syndrome is nowadays known as one of the most frequent reasons of long lasting discomfort and irritation of the eyes. From the clinical point of view, there are many etiologic causes, several combinations of anatomy pathologic manifestation and different grades of severity of dry eye diseases in the dysfunctional tear film syndrome. The ophthalmologist must recognize this three parameters, quantify them, and establish the most appropriate treatment. So, for this reason, in the 14th Congress of the Societas Ophthalmologica Europaea (Madrid, 2003), a multicenter study developed a practical classification of patients with ocular surface dryness based on etiology, histopathology and clinical severity of symptoms.